Missing Image of the Buddha in Early Buddhist Art: An Examination - Nitasha Joon (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2023)
The origins, motivations, and dates of the Buddha image's development are hotly contested topics. In general, the Buddha's image first appeared in two significant Kushana-era Indian art centers in the first few centuries of the common era. The ancient region of Gandhara, which encompasses parts of modern-day Pakistan and Afghanistan in addition to northwest India, was one hub of artistic production. The style of Gandharan images is similar to that of Hellenistic sculpture, and the presence of Hellenistic colonies as well as the extensive trade and exchange that took place in this crossroads of cultures undoubtedly had an impact on the artists in the area. People all over the world revere and adore the Buddha's serene face. But the eponymous image has enigmatic beginnings, and it wasn't until centuries after the Buddha's passing that it emerged as an artistic motif. This article answers the question, where did the image of the Buddha originate?